Transformasi Kurikulum Pendidikan Dasar di Era Society 5.0: Analisis Kesenjangan Digital dalam Implementasi Kurikulum di Indonesia - Nasrin Ameliasari; Syaiful Hadi; Muhammad Zaini (ARZUSIN, 2026)
The transformation of the basic education curriculum toward the Society 5.0 era requires inclusive technology integration; however, its implementation in Indonesia continues to face a digital divide that affects educational equity and quality. This study aims to analyze the transformation of the basic education curriculum in the Society 5.0 era, identify forms of the digital divide, analyze factors influencing successful implementation, and formulate conceptual recommendations for developing more inclusive and equitable curriculum policies. The study employed a Systematic Literature Review (SLR) approach based on the PRISMA 2020 guidelines through four stages: identification, screening, eligibility, and inclusion. The literature search was conducted across the Scopus, Google Scholar, Crossref, Dimensions, ERIC, and Garuda databases and yielded 18 articles that met the inclusion criteria and were published between 2023 and 2026. The synthesis results indicate that the digital divide in the transformation of the basic education curriculum is multidimensional and interrelated, encompassing limited digital infrastructure, teachers’ digital competence, inconsistencies in policy implementation across regions, and disparities in students’ digital literacy. Schools in frontier, outermost, and disadvantaged (3T) regions face multiple structural barriers, resulting in suboptimal implementation fidelity of the Kurikulum Merdeka, while teachers’ adaptive responses in practice tend to be individual and are not yet supported by systemic policy solutions. This study concludes that the successful transformation of the curriculum toward the Society 5.0 vision requires multilevel interventions that simultaneously encompass infrastructure improvement, the strengthening of teachers’ digital competence, and policy adaptation based on regional characteristics. These findings provide a conceptual foundation for developing more adaptive, inclusive, and equitable basic education curriculum policies and affirm that digital transformation cannot rely solely on the provision of learning platforms.